Portable Electronics Reimagined: Design, innovation, and user−centered solutions - Mădălina Elena Munteanu; Patricia Isabela Brăileanu (Journal of Research and Innovation for Sustainable Society)
Travelling is a fundamental activity for personal development, giving opportunities for exploring, learning and enrich the cultural knowledge. Especially for young travellers, the use of a backpack becomes a challenge due to its weight, limited space and the need of transporting only the essentials. In the same time, the reduce mobility and the insufficient comfort are elements that can cause the traveller experience. The project aims to reduce those obstacles by developing an innovating product which combines two of the most chosen electronics in travelling backpack: an iron and a hairdryer, integrating them into a compact, easy to carry and light device. This product not only saves space but also meets the need for comfort and convenience during travel. In technical terms, this project contributes to an ecological design process by reducing the materials used in manufacturing and minimizing the resources required for those products, individually. In a global context, where sustainability is crucial, the proposed project considers not only the immediate needs of users but also the protection of the planet’s resources for the future